EDUKASI PELAJAR TENTANG KEAMANAN CYBER DAN PERLINDUNGAN DATA PRIBADI - Lintang Raffi Nur Rizky; Safira Maulidia; Nabila Triyuni Kusniatin; Roky Alfarizi; Christensen Rozy Klaping; Qory Hidayatullah; Dewa Angelina Manurung; Tubagus Fauzan Akbar; Mohammad Satria; Ananda Hana Putra (Abdi Jurnal Publikasi, 2024)
In an increasingly digital era, understanding cyber security and personal data protection is very important, especially for students who are active users of technology. This research aims to provide education to students regarding the basic concepts of cyber security, threats they may face, and steps they can take to protect their personal data. The methods used in this research include counseling and distribution of interactive educational materials. The result of this activity is of course an increase in students' understanding of the importance of protecting personal information and data, as well as awareness of the risks associated with internet use. It is hoped that with the right education, students can become wiser and more responsible internet users, and be able to protect themselves from increasingly complex cyber threats